The Cost-Effectiveness of an Intervention Program to Enhance Adherence to Antihypertensive Medication in Comparison With Usual Care in Community Pharmacies - Bosmans, Judith E.; van der Laan, Danielle M.; Yang, Yuanhang; Elders, Petra J. M.; Boons, Christel C. L. M.; Nijpels, Giel; Hugtenburg, Jacqueline G. (Frontiers in Pharmacology, 2019)
Introduction Hypertension is considered an important public health issue. Inadequate disease management and non-adherence to antihypertensive medication may result in suboptimal clinical outcomes thereby imposing a financial burden on society. This study evaluates the cost-effectiveness of a patient-tailored, pharmacist-led intervention program aimed to enhance adherence to antihypertensive medication in comparison with usual care. Materials and methods An economic evaluation was conducted alongside a pragmatic randomized controlled trial with 9-months follow-up among 170 patients using antihypertensive medication. Effect outcomes included self-reported adherence (MARS-5), beliefs about medicines (BMQ Concern and Necessity scales) and quality-adjusted life-years (QALYs). Costs were measured from a societal perspective. Missing cost and effect data were imputed using multiple imputation. Bootstrapping was used to estimate uncertainty around the cost-differences and the incremental cost-effectiveness ratios. Cost-effectiveness planes and acceptability curves were estimated. Results There were no significant differences in costs or effects between the intervention program and usual care. The probability of cost-effectiveness of the intervention in comparison with usual care was 0.27 at a willingness-to-pay value of 0 €/unit of effect gained. At a willingness-to-pay value of 20,000 €/unit of effect gained, the probability of cost-effectiveness was 0.70, 0.27, 0.64, 0.87 and 0.36 for the continuous MARS-5 score, dichotomized MARS-5 score, BMQ Concern scale, BMQ Necessity scale and QALYs, respectively. Discussion In patients with hypertension, the patient-tailored, pharmacist-led intervention program to enhance medication adherence was not considered cost-effective as compared to usual care with regard to self-reported medication adherence, beliefs about medicines and QALYs.